Revisiting Qualification Standards for Local Candidates: Basis for Redefin-ing Social Media Campaign - Gajudo, Maria Bernadeth B.; Cariaga, Maria Josefina A. Bartolo; Laroco, Joana Marie V.; Suarez, Gemma R.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2024)
The study makes the case that adding social media campaign tactics to the requirements for local office holders will encourage more responsible, knowledgeable, and involved grassroots politics. This study explores the qualification standards for local candidates and how these standards can be redefined in the context of social media campaigns. As digital channels have a greater influence on voter involvement and perception, identifying the criteria that resonate with people becomes critical. The study highlights important characteristics—such as ethics, community involvement, and digital literacy—that distinguish successful local candidates. The study presents a methodology for optimizing campaign messaging and outreach by studying the candidates' successful social media techniques. Finally, the findings aim to help future politicians use social media to increase democratic engagement and develop meaningful ties with voters. This study emphasizes the essential interplay of candidate qualities and internet campaigning in determining electoral results.